MENGUNGKAP FAKTOR DETERMINAN PENGAMBILAN KEPUTUSAN KONSUMEN DALAM PEMBELIAN MAKANAN HALAL DI MAKASSAR - Aulia Fatimah Khairunnisa; Aminnullah Achmad Muttaqin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The demand for halal food is increasing among Muslim consumers worldwide, including in Makassar. Halal awareness and certification influence purchasing decisions, as the halal label provides safety assurance for Muslim and non-Muslim consumers. Price perception also affects buying decisions, as affordable prices are desired. Income also plays a role in consumer buying patterns and preferences. This research aims to analyze the impact of halal awareness, halal certification, price perception, and income on purchasing halal food in Makassar. The study employs a quantitative approach, gathering data through questionnaires distributed to 153 respondents who are halal food consumers in Makassar and aged above 18 years. The collected data will be analyzed using Ordinal Logistic Regression analysis. The research findings reveal that halal awareness, halal certification, and price perception positively and significantly impact the purchasing decisions of Makassar consumers when buying halal food. On the other hand, income does not significantly influence the decision to purchase halal food.